2014
DOI: 10.1097/rli.0000000000000011
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Controlled Aliasing in Parallel Imaging Results in Higher Acceleration in Gadoxetic Acid–Enhanced Liver Magnetic Resonance Imaging to Clarify the Hepatic Arterial Phase

Abstract: The CAIPIRINHA technique improved the image quality of hepatic arterial phase imaging with gadoxetic acid, reducing the number of non-diagnostic arterial phase studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 15 publications
3
40
1
Order By: Relevance
“…The acquired k-space samplings are offset from the normal grid-like sampling by shifting the sampling positions of alternate rows with respect to the partition-encoding direction (7,9,10). This technique can save the acquisition time and the breathholding time more effectively than the generalized auto calibrating partially parallel acquisition (GRAPPA) technique (8)(9)(10)13). In cooperative patients, our study showed that the 3D GRE with CAIPIRINHA was superior to 3D radial GRE with GA and ILAB for all qualitative analyses.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The acquired k-space samplings are offset from the normal grid-like sampling by shifting the sampling positions of alternate rows with respect to the partition-encoding direction (7,9,10). This technique can save the acquisition time and the breathholding time more effectively than the generalized auto calibrating partially parallel acquisition (GRAPPA) technique (8)(9)(10)13). In cooperative patients, our study showed that the 3D GRE with CAIPIRINHA was superior to 3D radial GRE with GA and ILAB for all qualitative analyses.…”
Section: Discussionmentioning
confidence: 93%
“…The newly developed, parallel acceleration technique (3D gradient recalled echo [GRE], with controlled aliasing in parallel imaging, resulting in higher acceleration [CAIPIRINHA]), can save image acquisition time, by modifying the phase encoding sampling manner, which leads to reduced aliasing artifacts and provides better image quality, although patients cannot hold their breath long enough (7)(8)(9)(10). Therefore, this rapid imaging technique that reduces respiration artifacts, may propel patients with short breathing capacity, into routine clinical MR practice.…”
Section: Introductionmentioning
confidence: 99%
“…Third, we could not compare the 3 datasets during arterial or portal phase in the same patients because the images dramatically change every second from arterial to venous phase in dynamic contrast-enhanced imaging. However, Tanimoto et al [19] reported that ringing artifacts could be reduced by a shorter scan time, and Park et al [13] reported that the CAIPIRINHA-VIBE with AF = 4 reduced the number of non-diagnostic arterial-phase images compared with the conventional protocols in different patients, with its already proven utility in dynamic contrast-enhanced imaging.…”
Section: Discussionmentioning
confidence: 97%
“…First, the 2-s difference in breath holding was not negligible for elderly patients. Second, parallel imaging artifacts and motion artifacts were difficult to exactly distinguish in some cases as discussed previously [13], and the score of motion artifacts might be slightly overestimated by parallel imaging artifacts. An acquisition time of approximately 10 s was thought to be suitable for the breath-hold examination especially for elderly patients, and further research on the most appropriate scan time is necessary.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation